Nanoporous aramid nanofibre separators for nonaqueous redox flow batteries - Siu on Tung (Nature Portfolio, 2018)
Nonaqueous redox flow batteries may offer high energy and power densities, but development of separators is key for optimization. Here the authors achieve high coulombic efficiency with a nanoporous aramid nanofibres-based separator with low permeability, high ion conductivity, and exceptional stability.